White Supremacy in the Movement Against the Prison-industrial Complex - Appel, Liz (Social justice, 2003)
Part of a special issue on war, dissent, and justice from the perspective of scholars, activists, and former U.S. political prisoners. Aspects of white supremacy have obstructed opportunities for change in the movement against the prison-industrial complex. White activists must be disciplined in their self-critique, continuously question their privilege and power, and accept that taking an antiracist stance is a process rather than a decision. They must also listen to the advice of white anti-imperialists with experience in antiracist struggles, who tell them to avoid adopting authoritarian and elitist models of organization.